Senecio imbaburensis, proposed name for Lasiocephalus sodiroi in the genus Senecio (Asteraceae) - Marhold, Karol; Sklenář, Petr (Phytotaxa, 2013)
Lasiocephalus Willd. ex Schlechtendal (1818: 308), as traditionally circumscribed (e.g., by Cuatrecasas 1978, Dušková et al. 2010), is a neotropical genus of ca 25 species confined to the Andes and distributed from Venezuela to Bolivia. Nevertheless, recent studies by Pelser et al. (2007, 2010) have shown that based on phylogenetic analyses of nrITS and plastid DNA sequence data, species of the genus Lasiocephalus are deeply embedded in Senecio Linnaeus (1753: 866), and, consequently, should be transferred into this latter genus. In fact, a number of species of Lasiocephalus were originally described as Senecio or had been, at some point, transferred into Senecio so only few transfers are necessary.